2023
DOI: 10.1186/s12870-023-04397-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saline water on soil properties and red radish growth in saline soil as a function of co-applying wood chips biochar with chemical fertilizers

Abu El-Eyuoon Abu Zied Amin

Abstract: Background Currently, using unconventional water sources in agriculture has become necessary to face overpopulation worldwide. Therefore, a pot experiment was carried out to evaluate the effects of irrigation with saline water in the presence of co-applied wood chips biochar (WCB) with chemical fertilizers on physicochemical properties and nutrient availability as well as growth parameters, and yield of red radish (Raphanus sativus L.) grown in the saline sandy soil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The effectiveness of biochar on soil properties is a multifactor phenomenon and depends on biochar synthetic methodology, soil type, biochar levels and so on 26 28 . The biochar applications have been known to influence nutrient applications, and the results are optimum if the BCs are prepared under the best conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of biochar on soil properties is a multifactor phenomenon and depends on biochar synthetic methodology, soil type, biochar levels and so on 26 28 . The biochar applications have been known to influence nutrient applications, and the results are optimum if the BCs are prepared under the best conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 39 . The increase in the rate of ABC might have caused the immobilization of soil N due to a higher C/N ratio than RSB 27 , 28 , 40 . Contrarily, Dempster et al 36 reported a significant decrease in net nitrification by applying Eucalyptus biochar (wood biochar) with increasing biochar addition in coarse-textured soils.…”
Section: Discussionmentioning
confidence: 99%
“…In the remediation of soils contaminated with polycyclic aromatic hydrocarbons and heavy metals, it was found that the relative abundance increase of Proteobacteria would lead to better remediation effects ( Kuppusamy et al, 2016 ). Under nutrient-rich conditions, Proteobacteria usually dominate among bacterial species, with a relatively high relative abundance ( Amin, 2023 ). However, sometimes there are differences ( Amin, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil available P was extracted with 0.5 mol L −1 NaHCO 3 [ 38 ]. In addition, soil available K was measured using flame photometry, which was extracted with 1 M ammonium acetate [ 39 ].…”
Section: Methodsmentioning
confidence: 99%